Effects of neurofeedback on the self-concept of children with learning disorders - Martínez-Briones, Benito Javier; Flores-Gallegos, Rodrigo; Cárdenas, Sonia Y.; Barrera-Díaz, Bertha Elena; Fernández, Thalía; Silva-Pereyra, Juan (Frontiers in Psychology, 2023)
Children with learning disorders (LDs) often have a lower self-concept than their typically developing peers. Neurofeedback (NFB) treatments seem to improve the cognitive and academic performance of these children, but the effects on self-concept have not been studied. In this exploratory study, 34 right-handed children (8–11 y.o.) with LD and delayed electroencephalographic maturation responded to the Piers–Harris Children’s Self-Concept Scale. One group received NFB (n = 20), and another group (n = 14) served as control, which included 9 children treated with sham-NFB and 5 on a waiting-list. A nonparametric permutation approach was used to compare the academic performance and self-concept difference (postscores – prescores) between the NFB and control groups. Given the smaller size of the control subgroups, a comparison of the percent changes between sham-NFB and the waiting-list was performed with the non-overlap of all pairs (NAP) technique. In the NFB group, the scores of reading, math, and global self-concept increased significantly, highlighting the self-concept subdomains of physical appearance, nonanxiety, popularity, and happiness. Additionally, the sham-NFB subgroup showed better outcomes than the waiting-list subgroup, perhaps due to noncontrolled factors. We found improved academic performance and self-concept in children with LDs who received NFB treatment. This study is an important exploratory step in studying a relevant treatment that seems to ameliorate symptoms of LDs such as anxiety and low self-concept.